Android-Based Learning Media to Improve Understanding of Indonesian Vocabulary - Mahardika, Putri Ayu; Sukardi (Jurnal Pendidikan dan Pengajaran, 2024)
Using Indonesian in official forums should be done, considering that Indonesian society consists of several regions with regional languages that may be different. The reality is that we still find teachers who use regional languages as the language of instruction when teaching in class. However, students need moreal understanding of Indonesian vocabulary, which makes their learning outcomes relatively low. This research aims to develop Android-based learning media to improve understanding of Indonesian vocabulary. This type of research is developed using the ADDIE model. This research used a pre-experimental design with a one-group pretest-posttest design, which was tested on students on a small and large scale, with the research subjects being class V students. The subjects of this research were material experts and media experts. Observation, interview, and questionnaire techniques were used for data collection. Data collection instruments used questionnaire sheets. The techniques used to analyze data are qualitative descriptive analysis and quantitative and inferential statistics. The results of the research were that the Teko application was proven to be feasible based on the results of validity tests by material experts and media experts. The Teko application received an assessment with very good criteria by users. Testing the effectiveness of the Teko application shows that the Teko application influences or improves student learning outcomes. It was concluded that the Teko application could improve understanding of Indonesian vocabulary.